Electronic word of mouth on social media websites: role of social capital theory, self-determination theory, and altruism. (20th December 2019) - Mahmood, Saqib; Khwaja, Muddasar Ghani; Jusoh, Ahmad
Purchase decisions in recent times are extensively dependent on social media referrals. The effective utilisation of social media has become compulsory for the organisations in order to remain competitive. In the emerging markets like Pakistan, promotions through electronic word of mouth on social media have incepted, but still it's quite difficult for the organisations to cope-up with the contemporary electronic word of mouth needs. Nevertheless, the Pakistani social media marketing managers are unfamiliar in motivating social media users to engage in electronic word of mouth. For that reason, the current research aims to understand the social capital theory and self-determination theory dimensions and altruism role in engaging customers for sharing products and services associated with word of mouth on social media websites. Structural, cognitive, and relational dimensions of social capital are manifested as tie-strength, shared language and trust respectively. Autonomy, competence, and relatedness of self-determination theory are manifested as voluntary self-disclosures, innovativeness, and trust respectively. In order to affirm literary associations among the constructs, structural equation modelling using MPlus was executed on the responses of 550 Pakistani social media users. The outcomes attained manifestly accepted the established hypotheses. Based on these findings theoretical and practical implications are produced.